The "footloose" mechanism:iceberg decay from hydrostatic stresses - Wagner, Till J. W.; Wadhams, P.; Bates, C. Richard; Elosegui, P.; Stern, A.; Vella, D.; Abrahamsen, E.P.; Crawford, A.; Nicholls, K.W. (Geophysical Research Letters, 2014)
We study a mechanism of iceberg breakup that may act together with the recognized melt and wave-induced decay processes. Our proposal is based on observations from a recent field experiment on a large ice island in Baffin Bay, East Canada. We observed that successive collapses of the overburden from above an unsupported wavecut at the iceberg waterline created a submerged foot fringing the berg. The buoyancy stresses induced by such a foot may be sufficient to cause moderate-sized bergs to break off from the main berg. A mathematical model is developed to test the feasibility of this mechanism. The results suggest that once the foot reaches a critical length, the induced stresses are sufficient to cause calving. The theoretically predicted maximum stable foot length compares well to the data collected in situ. Further, the model provides analytical expressions for the previously observed "rampart-moat" iceberg surface profiles.